2001
DOI: 10.1136/adc.85.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Dipstick measurements of urine specific gravity are unreliable

Abstract: Aim-To evaluate the reliability of dipstick measurements of urine specific gravity (U-SG). Methods-Fresh urine specimens were tested for urine pH and osmolality (U-pH, U-Osm) by a pH meter and an osmometer, and for U-SG by three diVerent methods (refractometry, automatic readout of a dipstick (Clinitek-50), and (visual) change of colour of the dipstick). Results-The correlations between the visual U-SG dipstick measurements and U-SG determined by a refractometer and the comparison of Clinitek ® -50 dipstick U-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…Our findings for the correlation of reagent strip with osmolality (R 2 5 0.67) are generally in agreement with previous studies (r: 0.61-0.83) (1,(8)(9)(10)12). It is thought that glucose does not affect the relationship between SG and osmolality (13,14) and it is controversial whether protein does so (5).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings for the correlation of reagent strip with osmolality (R 2 5 0.67) are generally in agreement with previous studies (r: 0.61-0.83) (1,(8)(9)(10)12). It is thought that glucose does not affect the relationship between SG and osmolality (13,14) and it is controversial whether protein does so (5).…”
Section: Discussionsupporting
confidence: 93%
“…This was true both for refractometry measured manually or by an automated refractometer as in our study (1,(8)(9)(10). In our study, we found a poorer correlation (r 5 0.73).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found, however, that urine creatinine <3 mM was more effective than urine SG ≤1.010 for identifying dilute samples in which random urinary PrCr was overestimated; the inaccuracy of urine dipstick SG compared to other measures of urine concentration is well documented [10], whereas the use of creatinine to correct for variability in urine concentration is the premise of PrCr assessment [1]. The overestimation is attributed to the fact that the accuracy of pyrocatechol violet molybdate dye-binding relies on the ionic strength of the urine.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 1 study had investigated the clinical performance of the urine reagent dipstick for measuring specific gravity in urine from dairy cattle; the results of that study indicated that the urine reagent dipstick measured 0.014 lower than U SG‐R . Urine specific gravity was poorly correlated ( r = 0.36) with U Osm in dog urine ( r = 0.39), and human urine . The dipstick pad has 3 main ingredients: a cation exchanger, pH color indicator (bromothymol), and buffers.…”
Section: Discussionmentioning
confidence: 99%